Meta-analysis of HLA-G 14bp insertion/deletion polymorphism and soluble HLA-G revealed an association with digestive cancers initiation and prognosis. Issue 7 (July 2022) - Dhouioui, Sabrine; Boujelbene, Nadia; Ouzari, Hadda-imene; Tizaoui, Kalthoum; Zidi, Inès
Abstract: Background/Objective: Conflicting results on the association between HLA-G and digestive cancers were reported. We conducted a meta-analysis to further investigate the true relationship between HLA-G and digestive cancers (DC). Methods: Following PRISMA guidelines, we performed a meta-analysis including 7 case-control studies on HLA-G 14-bp Insertion/deletion (I/D) polymorphism, and 15 studies on soluble HLA-G (sHLA-G). Odds ratios (OR) and their corresponding 95% confidence intervals (CI) for genetic polymorphisms were calculated. The pooled OR was calculated under three genetic models: allelic, recessive, and dominant models. Concerning sHLA-G meta-analysis, standardized mean differences (SMDs) were calculated. Results: The HLA-G 14-bp I/D was not associated with the risk of DC. However, in the subset of HBV/HCV positive hepato-cellular cancer (HCC) patients, we reported a significant association of HLA-G 14-bp I/D with the disease initiation under allelic (D vs. I; OR = 1.698, 95% CI = 1.263–2.282, p = 0.000), dominant (DD + ID vs. II; OR = 2.321, 95% CI = 1.277–4.218, p = 0.006)and recessive (DD vs. DI + II; OR = 1.739, 95% CI = 1.173–2.577, p = 0.006) genetic models. Interestingly, HLA-G 14-bp I/D was not associated with the disease initiation in HBV/HCV negative HCC patients. However, the infection by HBV/HCV seems to be implicated in the HCC development when we compared HBV/HCV positive patients to HBV/HCV negative patients under allelic (D vs. I; OR = 1.429, 95% CI = 1.029–1.983, p = 0.033, and dominant (DD + ID vs. II; OR = 1.981, 95% CI = 1.002–3.916, p = 0.049) genetic models. Overall analysis of DC showed significant increased sHLA-G in patients compared to healthy controls (SMD = 3.341, 95% CI = 2.415–4.267, p = 0.000). In Asian patients with gastric cancer, sHLA-G was significantly increased in grade 3 compared to low grades (SMD = 0.448, 95% CI = 0.109–0.787, p = 0.000). Further analysis showed that sHLA-G was significantly increased in positive DC vascular invasion (SMD = 0.743, 95% CI = 0.385–1.100, p = 0.000). Accordingly, sHLA-G was associated with a poor prognosis for DC. Conclusion: The current meta-analysis supports the significant role of HLA-G in DC. The HLA-G 14-bp I/D polymorphism was associated with HCC patients with concomitant HBV/HCV viral infections. Increased sHLA-G indicated a poor prognosis for DC cancer patients. Abstract : Digestive cancer; HLA-G; Polymorphism; sHLA-G; Meta-analysis.